Performance Analysis of Absorption Refrigeration Cycles Using DME or R600a and Squalane as Working Pair - Jia Xiucan; Luo Yong; Wang Xiaopo (Zhileng xuebao)
The thermodynamic performance of R600a/squalane and DME/squalane working pairs in single-effect and compression-assisted absorption refrigeration systems was analyzed in this study. The vapor-liquid equilibrium data were correlated using the NRTL model. The effects of the generation temperature, evaporation temperature, and compressor pressure ratio on the COP, exergy efficiency, and circulation ratio were analyzed. The results show that the R600a/squalane working pair performed better. The performance of the compression-assisted cycle was significantly better than that of the single-effect cycle. At an evaporation temperature of 278.15 K, peaks occur in the COP and exergy efficiency curves for single-effect and compression-assisted cycles with the increase in evaporation temperature. At a generation temperature of 363.15 K, the COP of the two working pairs increases monotonously with the increase in evaporation temperature, and the exergy efficiency curves exhibit peaks. With increasing generation and evaporation temperatures, the maximum COP and exergy efficiency values for the R600a and DME working pairs in the two cycles were 0.675 and 0.655, respectively. The performance of the DME working pair increased with an increase in the compression ratio, whereas that of the R600a working pair peaked at a ratio of 1.5. The circulation ratio decreased as the generation temperature, evaporation temperature, and pressure ratio increased.